Lesions of nasal cavity, paranasal sinuses and nasopharynx: a clinicopathological study - Kumar, Ambrish (International Journal of Medical Research and Review, 2016)
Background: A variety of non-neoplastic and neoplastic lesions of nasal cavity, paranasal sinuses and nasopharynx are commonly encountered in clinical practice. The aim of this study was to study clinical and histopathological profile of space occupying lesions of nasal cavity, paranasal sinuses and nasopharynx in a tertiary care hospital of Ranchi over the period of January 2011 to January 2012. Materials and Methods: This was a prospective study of 90 cases of space occupying lesions of nasal cavity, paranasal sinuses and nasopharynx over the period of 12 months. All tissues after fixation in 10% buffered formalin, processed and then stained with Hematoxylin & Eosin to study various histopathological patterns. Results: These 90 cases were broadly categorized in two categories, one category as nasal and paranasal sinus masses and the other as nasopharyngeal masses with 63 and 27 cases, respectively. These lesions were common in second and third decades of life with male predominance. Among nasal and paranasal sinus masses, there were 52 (82.2%) non-neoplastic and 11 (17.8%) neoplastic lesions. Inflammatory polyps (86.5%) were the most common among the non-neoplastic masses. Out of 27 nasopharyngeal masses, there were 23 (85.2%) non neoplastic and 4 (14.8%) neoplastic lesions. Majority of these i.e. 20 cases were of adenotonsillar hypertrophy. Conclusion: We concluded that complete clinical, radiological and histopathological correlation helps us to categorize these sinonasal lesions into various non-neoplastic and neoplastic types. But final histopathological examination provides a confirmatory diagnosis.